Policy Analysis of Indonesia's Sea Sand Export Reopening 2023 - Nur Al-Husin, Rachmasari (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
Abstract This research aims to analyze why Indonesia reopened the export of sea sand after being banned for 20 years. That in 2002, there was a policy banning the export of Indonesian sea sand because many were sent to Singapore and were detrimental. Then in 2007, another policy affirmation was issued to ban the export of sea sand. Until then in 2023, Indonesia reopened the export of sea sand. This research uses qualitative methods, through primary and secondary data sources. This research uses the concept of Domestic Source of Foreign Economic Policies by Michael J. Hiscox, related to what domestic sources influence foreign economic policies issued. Based on the results of the study, it can be found that the reason Indonesia issued a policy of reopening sea sand exports was based on preferences and institutions influence. Where preferences consist of trade, immigration, foreign investment, and exchange rates. While institutions consist of elections and representation, legislature and policy making, and bureaucratic agencies. Keywords: Indonesia, Singapore, Domestic Source of Foreign Economic Policies Abstrak Penelitian ini bertujuan untuk menganalisis mengapa Indonesia membuka kembali ekspor pasir laut setelah dilarang selama 20 tahun. Bahwa di tahun 2002, terdapat kebijakan pelarangan ekspor pasir laut Indonesia karena banyak dikirim ke Singapura dan merugikan. Kemudian di tahun 2007, dikeluarkan lagi penegasan kebijakan pelarangan ekspor pasir laut. Hingga kemudian di tahun 2023, Indonesia membuka kembali ekspor pasir laut. Penelitian ini menggunakan metode kualitatif, melalui sumber data primer dan sekunder. Penelitian ini menggunakan konsep Domestic Source of Foreign Economic Policies oleh Michael J. Hiscox, terkait sumber domestik apa saja yang mempengaruhi kebijakan ekonomi luar negeri dikeluarkan. Berdasarkan dari hasil penelitian, dapat ditemukan bahwa alasan Indonesia mengeluarkan kebijakan pembukaan kembali ekspor pasir laut dilandasi oleh adanya preferensi dan pengaruh institusi. Dimana preferensi terdiri dari perdagangan, imigrasi, investasi asing, dan nilai tukar. Sedangkan preferensi terdiri dari pemilihan umum dan representasi, legislatif dan pembuatan kebijakan, serta lembaga birokrasi. Kata kunci: Indonesia, Singapura, Domestic Source of Foreign Economic Policies